Exploring the Multifunctional PVC-DPG Polymer Complexes: Synthesis, Characterization and Evaluation of the Antibacterial Activity - Al-Ani, Ahmed (Al-Nahrain Journal of Science, 2024)
Polyvinyl chloride (PVC) has attracted great attention because of its applications in different fields such as industrial and medical fields. In this work PVC has been reacted with diphenylglyoxime (DPG) in Tetrahydrofuran (THF) to form PVC–DPG polymer, then the synthesized polymer reacted with alcoholic solutions of different metal ions (Fe(II), Co(II), Ni(II), Pd(II), Pt(IV) and Cu(II) to form colored metal ion complexes. All compounds are characterized by Fourier-transform infrared (FTIR), Ultraviolet (UV-Vis) spectroscopies, magnetic susceptibility and conductivity measurements. All complexes were examined with staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative), confirming the biological activity against these bacteria.